Association of consanguineous marriages with severe early childhood caries: a pilot study - Aras, Ahmet; Doğan, Mehmet Sinan; Yıldız, Şemsettin; Demir, Muhammed (Harran Üniversitesi, 2022)
Objective: Consanguineous marriages have been reported to cause various genetic problems and lead to a number of syndromes, including dental syndromes that can result in dental caries. The aim of this pilot study was to determine whether consanguineous marriage is a predisposing factor for severe early childhood caries (S-ECC). Methods: Ninety S-ECC patients aged 36–71 months were included in the study. Patients were divided into two groups; first group included children of first-cousin consanguineous marriages (n1 = 45), and the second group comprised children whose parents did not have consanguineous marriages (n2 = 45). Dental caries were recorded by two experienced paediatric dentists using the dmft index based on the ICCMS™ criteria. Between-group comparisons of dmft data were carried out using the Mann–Whitney U-test. Results: The 90 paediatric patients in this study included 42 (46.7%) females and 48 (53.3%) males with a mean age of 4.39 ± 1.07 years. The median dmft value for Group 1 was 9 (5-14) and 8 (5-15) for Group 2. However, this difference was not statistically significant (p>0.05). Conclusion: Although the median dmft score was found to be higher in children with consanguineous parents, this difference was not statistically significant.
Keywords: Dentistry; Diş Hekimliği